Association between outpatient visits for pterygium and air pollution in Hangzhou, China. (15th December 2021) - Fu, Qiuli; Mo, Zhe; Gu, Yuzhou; Lu, Bing; Hao, Shengjie; Lyu, Danni; Xu, Peiwei; Wu, Lizhi; Lou, Xiaoming; Jin, Hongying; Wang, Xiaofeng; Chen, Zhijian; et al.
Abstract: Air pollution could be a risk factor for the development of pterygium. This study aimed to investigate the potential associations between outpatient visits for pterygium and air pollutants. Using a time-stratified case-crossover design, the data of 3017 outpatients with pterygium visiting an eye center in Hangzhou, China, and the air pollution data of the Environmental Protection Department of Zhejiang Province between July 1, 2014, and November 30, 2019, were examined. The relationships between the air pollutants nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), ozone, and fine particulate matter (PM) with median aerometric diameter <2.5 μm (PM2.5 ) and <10 μm (PM10 ) and outpatient visits for primary pterygium were assessed using single- and multiple-pollutant models. Significant associations between outpatient visits for pterygium and air pollutants (PM2.5, PM10, SO2, and NO2 ) were observed. Younger patients were found to be more sensitive to air pollution. Interestingly, the younger female patients with pterygium were more vulnerable to PM2.5 exposure during the warm season, while the younger male patients with pterygium were more sensitive to NO2 during the cold season. Significant effects were also observed between the pterygium outpatients and PM2.5 (odds ratio [OR] = 1.06, P  = 0.02), PM10 (OR = 1.04, P  = 0.01), and SO2 (OR = 1.26, P  = 0.01) during the warm season, as well as NO2 (OR = 1.06, P  = 0.01) during the cold season. Our study provides evidence that outpatient visits for pterygium are positively associated with increases in the air pollutants PM2.5, PM10, SO2, and NO2, revealing the important role of air pollution in the occurrence and development of pterygium. Graphical abstract: Image 1 Highlights: Air pollutants are in significant associations with outpatient visits for pterygium. Younger pterygium patients are more sensitive to air pollution. The female pterygium patients are more vulnerable to PM2.5 during the warm season. The male pterygium patients are more sensitive to NO2 during the cold season.